FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN OPINI AUDIT GOING CONCERN - Astari, Putu Wasita; Latrini, Made Yeni (E-Jurnal Akuntansi; Vol 19 No 3 (2017), 2017)
The purpose of this study is to show the effect of disclosure, debt default, the audit quality and audit opinion the previous year on a going-concern audit opinion. The population in this study are all companies listed on the Indonesia Stock Exchange for the period 2012-2015. Sampling method used is purposive sampling method, with a total sample of 124 with 31 companies selected. Data analysis technique used is the logistic regression (logistic regression). Based on the results of the analysis showed that the variables of disclosure does not affect the going concern audit opinion. Debt default does not affect the going concern audit opinion. Audit quality has no effect on the going concern audit opinion. The audit opinion the previous year affect the going concern audit opinion.
Keywords: Disclosure, Debt Default, Quality Audit, Audit Opinion Previous Year, Going Concern